Impact of first-line infliximab on the pharmacokinetics of second-line vedolizumab in inflammatory bowel diseases. Issue 6 (July 2019) - Liefferinckx, Claire; Verstockt, Bram; Gils, Ann; Tops, Sophie; Van Moerkercke, Wouter; Vermeire, Severine; Franchimont, Denis
Background: Very little is known about the impact of the wash-out period on the pharmacokinetics of a second-line biologic. Objective: The objective of this article is to explore the impact of two different wash-out periods on the pharmacokinetics of vedolizumab and infliximab. Methods: Patients switching from infliximab to vedolizumab were retrospectively identified. The population was divided into two groups according to wash-out period: <6 weeks or >6 weeks. Vedolizumab and infliximab trough levels (TLs) were determined and correlated with clinical and biological outcomes. Results: A total of 71 inflammatory bowel disease patients were included. At week 6, in patients previously treated with infliximab, median vedolizumab TLs were 21.9 µg/ml and 24.9 µg/ml for the <6 weeks and >6 weeks wash-out period, respectively ( p  = 0.31), whereas median residual infliximab TLs were 0.5 µg/ml and 0 µg/ml ( p  = 0.034). The rate of treatment discontinuation was similar ( p  = 0.64), and the infectious events were six and two for the <6 weeks and >6 weeks wash-out period, respectively ( p  = 0.12) by week 30. Conclusions: This study suggests clinicians may not need to be concerned about the impact of wash-out period on the pharmacokinetics of the second-line biologic when switching infliximab to vedolizumab. More data are required on the impact of wash-out period on safety.